Mapping of a replication origin within the promoter region of two unlinked, abundantly transcribed actin genes of Physarum polycephalum. - Bénard, M (1996)
We analyzed the replication of two unlinked actin genes, ardB and ardC , which are abundantly transcribed in the naturally synchronous plasmodium of the slime mold Physarum polycephalum. Detection and size measurements of single-stranded nascent replication intermediates (RIs) demonstrate that these two genes are concomitantly replicated at the onset of the 3-h S phase and tightly linked to replication origins. Appearance of RIs on neutral-neutral two-dimensional gels at specific time points in early S phase and analysis of their structure confirmed these results and further established that, in both cases, an efficient, site-specific, bidirectional origin of replication is localized within the promoter region of the gene. We also determined similar elongation rates for the divergent replication forks of the ardC gene replicon. Finally, taking advantage of a restriction fragment length polymorphism, we studied allelic replicons and demonstrate similar localizations and a simultaneous firing of allelic replication origins. Computer search revealed a low level of homology between the promoters of ardB and ardC and, most notably, the absence of DNA sequences similar to the yeast autonomously replicating sequence consensus sequence in these Physarum origin regions. Our results with the ardB and ardC actin genes support the model of early replicating origins located within the promoter regions of abundantly transcribed genes in P. polycephalum.